COEXISTENCE OF KAHARINGAN, FAITHS AND CULTURES: REVISITING IMAGINATIVE IMMANUEL KANT - Nia Desiska; Oktalia, Linda Lestari Kueain, Tri Sugianto, Melin, Nova Lady Simanjuntak, Aprianto Wirawan (ADISAM Publisher, 2024)
The purpose of this writing is to describe how far the development of Christianity in Tribal Religious civilization, especially in the Dayak Tribe (Kaharingan) or known as the Helu religion. The authors analyzes and describes according to the perspective of Immanuel Kant. Immanuel argues that both Christianity and tribal religions must be able to understand and place a religion logically and morally. The research method used is the phenomenological quantitative research method, and analyzing journals. Kant's rational criticism has the potential to improve the understanding of one's religious logic and morals because basically Kant wants to provide an understanding to religious adherents so that they can understand the teachings of a religion using morals and logic so that they have an impact on the surrounding environment and bring good changes to everyone.